The Current State and Prospects for the Development of Akmola Region as a Tourism Destination - MUSSINA, Kamshat; DULATBEKOVA, Zhanar; BAIMBETOVA, Assel; PODSUKHINA, Olga; LEMANOWICZ, Marzena (Journal of Environmental Management and Tourism; Vol 10 No 8 (2019): JEMT Volume X Issue 8(40) Winter 2019DO - 10.14505//jemt.v10.8(40).23, 2020)
Formation of modern tourism industry as a complex economic, social and environmental system is based on the interaction between tourists and tourism destinations. A tourism destination acts as a key component of the whole tourism system, since it is formed by functionally related elements (tourism resources, tourism and the general infrastructure of the territory, labor potential and governing bodies), which are located within a certain territory, have information and communication structures to ensure the implementation of production strategies and tactics. The article summarizes the main theoretical approaches to determining the essence of the economic category “tourism destination”. The characteristic of the main approaches to the content of tourism destinations is given. The authors’ approach to the structure and components of tourism destinations is proposed. A statistical analysis of trends and dynamics of tourism development in the Akmola region is presented. Based on the study, a model is proposed, the use of which can significantly increase the influx of tourists into the Akmola region as a tourism destination.